Penerapan Strategi Permainan Bisik Kalimat Berantai dalam Meningkatkan Minat Belajar Siswa pada Pembelajaran Bahasa Arab di MA Darul Hikmah Kota Bima - Muhammad Fadiel Rohmani; Muslimin Muslimin; Muh. Zulkarnain (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aimed to determine the effectiveness of the whisper chain sentence game strategy in improving students’ learning interest in Arabic language learning at MA Darul Hikmah Kota Bima. This research employed the Classroom Action Research (CAR) method based on the Hopkins model, which was conducted in one cycle, namely Cycle I. The participants of this study consisted of 12 students of class X-B. Data were collected through observation, questionnaires, and documentation. Furthermore, the data were analyzed using quantitative and qualitative descriptive techniques by calculating the class percentage scores and the level of improvement in students’ learning interest at each stage of the research. The findings revealed that the implementation of the whisper chain sentence game strategy successfully improved students’ learning interest in Arabic language learning. In the pre-cycle stage, the total score obtained by the students was 377 with a learning interest percentage of 65.45%, which was categorized as sufficient. After the implementation of the strategy in Cycle I, the total score increased to 505 with a percentage of 87.67%, which was categorized as very good. The improvement was reflected in students’ increased attention, enthusiasm, participation, and active involvement during the learning process. Therefore, the whisper chain sentence game strategy can be used as an effective, interactive, and enjoyable alternative learning strategy to improve students’ learning interest in Arabic language learning.